Green infrastructure: The future of urban flood risk management?. (27th September 2021) - Green, Daniel; O'Donnell, Emily; Johnson, Matthew; Slater, Louise; Thorne, Colin; Zheng, Shan; Stirling, Ross; Chan, Faith K. S.; Li, Lei; Boothroyd, Richard J.
Abstract: Urban flooding is a key global challenge which is expected to become exacerbated under global change due to more intense rainfall and flashier runoff regimes over increasingly urban landscapes. Consequently, many cities are rethinking their approach to flood risk management by using green infrastructure (GI) solutions to reverse the legacy of hard engineering flood management approaches. The aim of GI is to attenuate, restore, and recreate a more natural flood response, bringing hydrological responses closer to pre‐urbanized conditions. However, GI effectiveness is often difficult to determine, and depends on both the magnitude of storm events and the spatial scale of GI infrastructure. Monitoring of the successes and failures of GI schemes is not routinely conducted. Thus, it can be difficult to determine whether GI provides a sustainable solution to manage urban flooding. This article provides an international perspective on the current use of GI for urban flood mitigation and the solutions it offers in light of current and future challenges. An increasing body of literature further suggests that GI can be optimized alongside gray infrastructure to provide a holistic solution that delivers multiple co‐benefits to the environment and society, while increasing flood resilience. GI will have to work synergistically with existing and upgraded gray infrastructure if urban flood risk is to be managed in a futureproof manner. Here, we discuss a series of priorities and challenges that must be overcome to enable integration of GI into existing stormwater management frameworks that effectively manage flood risk. This article is categorized under: Engineering Water > Sustainable Engineering of Water Engineering Water > Planning Water Science of Water > Water Extremes Abstract : Global distribution of notable urban stormwater management GI schemes and examples of different GI systems.